A competency framework for clinical pharmacists and heart failure. (20th July 2018) - Forsyth, Paul; Warren, Alison; Thomson, Clare; Bateman, Joanne; Greenwood, Elizabeth; Williams, Helen; Khatib, Rani; Hadland, Rocco; McGlynn, Steve; Khan, Nazish; Duggan, Catherine; Beezer, Janine; et al.
Abstract: Objectives: Heart failure is an escalating 'pandemic' with malignant outcomes. Clinical pharmacist heart failure services have been developing for the past two decades. However, little clarity is available on the additional advanced knowledge, skills and experience needed for pharmacists to practice safely and competently. We aimed to provide an expert consensus on the minimum competencies necessary for clinical pharmacists to deliver appropriate care to patients with heart failure. Methods: There were four methodological parts; (1) establishing a project group from experts in the field; (2) review of the literature, including existing pharmacy competency frameworks in other specialities and previous heart failure curricula from other professions; (3) consensus building, including developing, reviewing and adapting the contents of the framework; and (4) write‐up and dissemination to widen the impact of the project. Key findings: The final framework defines minimum competencies relevant to heart failure for four different potential levels of specialism: all pharmacists regardless of role (Stage 1); all patient‐facing clinical pharmacists (Stage 2); clinical pharmacists with specific planned roles in the care of heart failure patients (Stage 3); and regionally/nationally/internationally recognised expert pharmacists with a direct specialism in heart failure (Stage 4). Conclusions: The framework delivers the vital first step needed to help standardise care, give pharmacists a blueprint for career progression and continuing professional development and bring clarity to the role of the pharmacist. Future collaboration between professional bodies and training providers is needed to develop structured programmes to align with the framework and facilitate training and resultant accreditation.